Socio-political tensions in Bus Rapid Transit (BRT) development in low-income Asian cities. Issue 1 (2nd January 2019) - Wijaya, Suryani; Imran, Muhammad; McNeill, Jeffrey
ABSTRACT: International development agencies, with the help of the central government, support building state of art Bus Rapid Transit (BRT) in low-income Asian cities. However, BRT investment over indigenous modes of mobility is creating socio-political tensions at the local level. This article uses multi-level governance as a theoretical lens to examine the relationships among actors in BRT investment decisions in Bandung and Surabaya, Indonesia. The research finds that local stakeholders can distort national and supranational policy initiatives totally or in a way that while projects are delivered, they are of limited use to the local communities they intended to help.